Pengembangan Media Pembelajaran berbasis Android untuk Materi Pemrograman Dasar di SMK Negeri 5 Malang - Mochammad Hafidz; Wibisono Sukmo Wardhono; Satrio Agung Wicaksono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
How easy access to learning media in a smartphone will make students often accessing the available media to increase students learning interest and learning results.